Hierarchical NiCo2O4/NiFe/Pt heterostructures supported on nickel foam as bifunctional electrocatalysts for efficient oxygen/hydrogen production. Issue 60 (29th October 2019) - Huang, Qingyou; Cao, Yang; Wang, Xiaohong; Tu, Jinchun; Xia, Qianfeng; Wu, Qiang
Abstract : (a) LSV of overall water splitting for the respective component at a scan rate of 5 mV s −1 . (b) Chronopotentiometry curve under a constant current density of 20 mA cm −2 . Inset: photographic image of two-electrode water electrolysis device. Abstract : As the demand for clean and renewable energy increases, high-efficiency multifunctional electrocatalysts for water cracking have become a research hotspot. In this study, a NiCo2 O4 /NiFe/Pt composite with a hierarchical structure was successfully constructed by combining a hydrothermal growth and electrodeposition method with nickel foam as the scaffold material, and its overall water cracking reaction was studied. The laminar-structured NiCo2 O4 /NiFe composite exhibits an improved number of electrochemically active sites and shorter electron transport pathways, while the Pt particles deposited on the NiCo2 O4 /NiFe composite are conducive to improve the hydrogen evolution reaction without affecting the efficiency of the oxygen evolution reaction of the intrinsic material. The NiCo2 O4 /NiFe/Pt composite shows an excellent overall water cracking performance under alkaline conditions with a current density of 10 mA cm −2 at an applied potential of 1.45 V, indicating a promising research prospect.